Triptans for Acute Migraine: Drug Class Review to Help Inform Policy Decisions. (14th July 2015) - Knowles, Sandra; Oh, Paul; Gomes, Tara; ,
Abstract : Background/Objective: In Ontario, triptans are publicly funded through the Ontario Drug Benefit's Exceptional Access Program, a prior authorization program. However, it was unclear whether this listing aligned with current evidence of safety and effectiveness for triptans in migraine. Using a comprehensive and novel drug class review framework, we describe our review of triptans for the management of acute migraine to evaluate the appropriateness of triptan listing on the public drug formulary in Ontario. Methods: This supplement in H eadache highlights four key components of the triptan drug class review, including findings from a qualitative analysis of patient and clinician perspectives, a systematic review and network meta‐analysis of clinical trial evidence, a pharmacoepidemiologic analysis comparing utilization trends across Canada, and a reimbursement‐based economic analysis. Results: We found that triptans were efficacious and safe for the treatment of acute migraine. However, Ontario has among the lowest rates of publically funded triptan use in Canada, which may be due to the highly restrictive nature of access to triptans in Ontario. Expanding access to triptans via a less restrictive listing (eg, Limited Use) would potentially increase use by 20‐fold, with increase in costs of approximately 220%. Conclusion: Based on findings from our multi‐faceted review and after stakeholder review and input from the Citizens' Panel, two policy options for triptans were recommended for Ontario's publically funded drug program: Limited Use access or coverage via the Exceptional Access Program, both options including quantity limits of 12 units per month.